Prevalence of Chronic Obstructive Pulmonary Disease in Lung Cancer Patients in Dr. M Djamil General Hospital - Junaidi, Katerine; Khairsyaf, Oea; Ermayanti, Sabrina; Yunus, Faisal; Herman, Deddy (South Eastern European Journal of Public Health, 2025)
Background: The prevalence of COPD is high in lung cancer patients ranging from 40-70%, but is often undiagnosed due to similar risk factors and chronic respiratory symptoms. Chronic obstructive pulmonary disease not only contributes to the occurrence of lung cancer but can also be an overlapping condition that affects prognosis and treatment options. Methods: A descriptive-analytic study with a cross-sectional design was conducted on lung cancer patients who had known cell types at the polyclinic of Dr. M Djamil Padang Hospital and spirometry examination was performed. Results: Total 49 subjects with 77.6% male, 40-59 years old (46.9%), former smokers (73.5%) with severe Brinkman index (IB) (78.9%). The most common type of lung cancer was squamous cell carcinoma (61.2%) and most subjects were at an advanced stage (83.6%) with ECOG clinical appearance 1 (79.6%). The location of lung cancer lesions was predominantly central (83.7%) with restriction lung function values (98%) and 37.5% of them with obstruction. The prevalence of COPD in lung cancer patients was 34.7% with patient characteristics mainly male (88.2%), 60-79 years (58.8%), former smokers (82.4%) with severe IB (86.7%). The types of lung cancer of subjects with COPD were mainly squamous cell carcinoma (52.9%), advanced stage (76.5%), ECOG 1 (70.6%) and centralized (94.1%). The degree of obstruction in the COPD group was mainly GOLD 2 (41.2%) with population group E (64.7%). There was no association between the type, staging, and location of lung cancer lesions with the degree of obstruction or with the COPD population group Conclusion: Lung cancer patients with COPD are mainly male with an older age, the most common type is squamous cell carcinoma, advanced stage, with central lesion all lung cancer patients with COPD in the study were undiagnosed COPD cases.